Seizure Prophylaxis in Neurocritical Care: A Review of Evidence‐Based Support. Issue 4 (26th November 2013) - Rowe, A. Shaun; Goodwin, Haley; Brophy, Gretchen M.; Bushwitz, Jennifer; Castle, Amber; Deen, David; Johnson, Dachelle; Lesch, Christine; Liang, Norah; Potter, Emily; Roels, Christina; Samaan, Karen; et al.
<x xml:space="preserve">Abstract</x> Seizures are a well‐described complication of acute brain injury and neurosurgery. Antiepileptic drugs (AEDs) are frequently utilized for seizure prophylaxis in neurocritical care patients. In this review, the Neurocritical Care Society Pharmacy Section describes the evidence associated with the use of AEDs for seizure prophylaxis in patients with intracerebral tumors, traumatic brain injury, aneurysmal subarachnoid hemorrhage, craniotomy, ischemic stroke, and intracerebral hemorrhage. Clear evidence indicates that the short‐term use of AEDs for seizure prophylaxis in patients with traumatic brain injury and aneurysmal subarachnoid hemorrhage may be beneficial; however, evidence to support the use of AEDs in other disease states is less clear.